A Biomechanical Analysis of Tibial Fixation Methods in Hamstring-Graft Anterior Cruciate Ligament Reconstruction - Fogel, H. (Iowa Orthop J, 2019)
BACKGROUND: There are conflicting results on the biomechanical properties of tibial fixation devices in anterior cruciate ligament reconstruction. The objective of this study is to compare the initial biomechanical properties of tibial fixation in hamstring-graft ACL reconstruction with interference screw, suspension button, and Tape Locking Screw(TM) devices. We hypothesized there are no differences in the initial biomechanical properties of these three tibial fixation techniques. METHODS: Twenty-one fresh-frozen porcine tibiae were equally divided into three groups of seven tibiae to evaluate the fixation of human hamstring tendon grafts with interference screw, suspension button, or Tape Locking Screw fixation. Using a servohydraulic materials testing system, each graft was subjected to 500 cycles of loading followed by a monotonic failure test. RESULTS: Interference screw fixation demonstrated significantly lower cyclic displacement (1.28 ± 0.73 mm) than the other groups fixated with either a suspension button device (2.54 ± 0.27 mm, p = 0.003) or a Tape Locking Screw (2.32 ± 0.42 mm, p = .009), and a significantly greater cyclic stiffness (212.19 ± 40.30 N/mm) than the Tape Locking Screw (137.64 ± 26.17 N/mm, p = 0.002). The interference screw also demonstrated significantly higher pullout stiffness (166.83 ± 23.22 N/mm) than the suspension button (112.78 ± 24.14 N/mm, P = 0.002) and Tape Locking Screw (109.11 ± 12.91 N/mm, P = 0.0002). CONCLUSIONS: Tibial fixation with an interference screw demonstrated superior biomechanical properties for cyclic testing compared to the suspension button and Tape Locking Screw. Load to failure did not differ between groups, and there were no significant biomechanical differences between the suspension button and Tape Locking Screw fixation devices. CLINICAL RELEVANCE: Despite the initial biomechanical differences, all three fixation devices exhibited mean loads to failure and cyclic displacements below clinically relevant thresholds of failure. These data suggest all three fixation methods are viable options for achieving a functional ACL reconstruction. Level of Evidence: V